Evaluating the effect of active riparian rehabilitation initiatives and investment on native vegetation recovery, in the Berg-Breede catchment, Western Cape, South Africa - Van Zitters, Monique (Stellenbosch : Stellenbosch University, 2021)
Thesis (MScConsEcol)--Stellenbosch University, 2021.